Law and Islam in the Middle East: By Daisy Hilse Dwyer (ed). Law and Islam in the Middle Fast. Westport, CT: Greenwood Press, 1990, 168 pp. (American Journal of Islam and Society, 1992)
This is a collection of anthropological studies on the dynamics of the implementationoflaw in the Middle East. The basic arguments of the book raisethe issue of the context of law and the role of Islamic law in the Middle East.The editor, Daisy Dwyer, contends that context rather than the letter of the lawis the core phenomenon determining the handling and outcome of legal cases.The form and impact of Islamic law varies according to the specific regionaland cultural context . Dwyer also argues that Islamic law is often invoked notso much for its specific content but as a political symbol relating the past tothe present and, ultimately, the future.These points are significant for understanding the impact of Islamic lawin the Middle East. The cultural context will consistently influence which proBookvisions of the law are emphasized and which provisions are deemphasized orconveniently forgotten. Furthermore, social outlooks and cultural habits willin turn impact upon huw the specific provisions are interpreted and implemented.As Safia Mohsen demonstmtes in an insightful article on mmen and the criminaljustice system in Egypt, the implementation of law responds to the specific situationof women in Egypt. The way criminal law is implemented sometimesdiscriminates, depending on the context, in favor of or against women ...